The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1093/jnci/85.12.979
|View full text |Cite
|
Sign up to set email alerts
|

Noncancer Deaths in White Adult Cancer Patients

Abstract: Because more noncancer deaths occurred shortly after diagnosis, it appears that this excess was caused by treatment of the cancer. Generally, cancer-specific death rates underestimate the mortality associated with a diagnosis of cancer. Therefore, because the degree of underestimation changes with time, an examination solely of cancer-caused mortality in assessing progress against the disease is incomplete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
156
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(162 citation statements)
references
References 0 publications
6
156
0
Order By: Relevance
“…Cancer is the underlying cause of death among the vast majority of women with cancer (2, 3). The underlying cause of many "non-cancer" deaths can often be associated directly with nontreatment or even with some cancer treatment complications (35). Although length of survival is highly accurate in these cancer registries, the underlying cause of death is not (14).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is the underlying cause of death among the vast majority of women with cancer (2, 3). The underlying cause of many "non-cancer" deaths can often be associated directly with nontreatment or even with some cancer treatment complications (35). Although length of survival is highly accurate in these cancer registries, the underlying cause of death is not (14).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is the underlying cause of most deaths among younger women with breast cancer [26,27]. Moreover, the underlying cause of many "non-cancer" deaths can often be directly associated with non-treatment or even with some cancer treatment complications [63]. And this study's hypothesized African American disadvantage among younger women was not only observed for survival, but also for receipt of a number of treatments.…”
Section: Study Limitations and Strengthsmentioning
confidence: 86%
“…16 Men with prostate cancer have higher rates of non-cancer mortality than do men in the general population, and some of the excess non-cancer deaths may be treatment-induced. 17 In men undergoing ADT, metabolic changes are observed often, which may lead to an increased risk of type 2 diabetes, cardiovascular diseases and metabolic syndrome and might contribute to the increase of non-cancer deaths. 18 A review of the literature suggests that male hypogonadism is accompanied by an increased risk of insulin resistance and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%